Heterosis in Local Boro Rice (Oryza sativa L.) - Islam, MM; Sarker, U; Rasul, MG; Rahman, MM (Bangladesh Journal of Plant Breeding and Genetics, 2011)
An experiment was conducted to study the heterosis of 27 F1 hybrids produced from nine CMS lines and three restorer lines of rice with their parental lines and BRRI Dhan29 as standard check for 17 yield and its contributing traits. Mid parent, better parent and standard heterosis of most of the crosses were significant for most of the characters studied either in positive or in negative direction. Desirable and significant mid parent and better parent heterosis was observed in 13 and seven cross combinations, respectively for grain yield and most of its related traits. Considering more than 20% mid parent and better parent heterosis for grain yield along with most of its related traits, nine and five cross combinations, respectively were identified as good heterotic combinations over mid parental and better parental value. On the basis of individual trait significant and desirable mid parent heterosis was observed in eight cross combinations for plant height, 12 for leaf blade length, nine for flag leaf blade length, 13 for flag leaf sheath length, eight for tillers per hill, eight for panicles per hill, 14 for days to 50% flowering, four for days to maturity, four for panicle length, 14 for panicle weight, nine for primary branches per panicle, 16 for secondary branches per panicle, six for filled grains per panicle, 15 for 1000 seed weight, 13 for grain yield per hill and 15 for harvest index. Significant and desirable better parent heterosis was observed in 12 cross combinations for plant height, 11 for leaf blade length, 5 for flag leaf blade length, nine for flag leaf sheath length, seven for tillers per hill, seven for panicles per hill, 25 for days to 50% flowering, one for days to 100% flowering, seven for days to maturity, three for panicle length, nine for panicle weight, five for primary branches per panicle, 12 for secondary branches per panicle, four for filled grains per panicle, nine for 1000 seed weight, seven for grain yield per hill and nine for harvest index. None of the crosses were identified as good heterotic over standard check for grain yield per hill but many good and desirable heterotic crosses were identified over standard check for most of the yield related characters. Twenty cross combinations were identified as heterotic over standard check due to desirable and significant standard heterosis for most of the yield related traits. Keywords: Heterosis; rice; Oryza sativa; boro DOI: http://dx.doi.org/10.3329/bjpbg.v23i1.9314 BJPBG 2010; 23(1): 19-30